Central American flash-fiction: a first look at the genesis and characteristics of the short narrative format of the region - Sánchez Argüello, Alberto (2022)
This article explores the panorama of flash-fiction in six Spanish-speaking countries of the Central American: Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica and Panama, with the aim of having a first look at the comparative genesis of regional flash-fiction, its state current situation and the characteristics of minifictional creation in Central America.